Twins - "Watson, Peter" (London, 1981)
Identical twins are scarce enough; identical twins adopted into different families even rarer still. Now scientists at the University of Minnesota have been able to find sixteen pairs of identical twins who grew up apart. Their lives show the most startling coincidences: the twins who brought the same make of diary the same ( and only) year- and filled in entries for the same dates: the twins who drive identical cars across America each year- to holiday on the same tiny stretch of beach; the twins who arrived at Minneapolis and found the other was wearing just the same clothes, or just the same jewelry.
Keywords: Twins Psychology